Comparison of inflammatory parameter levels after sclerotherapy of varicose veins with polidocanol - Anel Okic; Magrin Alic; Hasib Mujic; Amel Hadzimehmedagic; Nermina Babic; Nesina Avdagic (Medicinski glasnik, 2026)
OBJECTIVE: To determine changes in inflammatory parameter values ​​after foam sclerotherapy of varicose vein. The values ​​of inflammatory parameters were taken and compared immediately after treatment and seven days after treatment. METHODS: A total of 41 patients with verified varicose vein disease were included in this study. They were monitored immediately after treatment and seven days after treatment. Samples were taken from the cubital vein and 82 samples were analyzed. The following values ​​were measured: C-reactive protein, D-dimer, fibrinogen and leukocytes. RESULTS: Only positive results and significant differences were observed in D-dimer values. Significant changes were recorded in D-dimer levels, which showed significant increases 7 days after treatment. D-dimer levels increased from an average of 287.3 ng/ml to 350.9 ng/ml, which is a statistically significant change with a p-value of 0.04. The difference was not statistically significant for other parameters. CONCLUSION: D-dimers have been shown to be a specific inflammatory parameter in veins sclerotherapy. Increased values ​​did not affect blood hypercoagulability. Sclerosing agents are effective for seven days after treatment, and recovery should be adjusted to this finding. Although an increase in D-dimer values ​​has been proven, veins sclerotherapy treatment is a safe, extremely effective and reliable method of treating varicose veins, and will have an increasingly wide usage in future.
Keywords: C-reactive protein; D-dimer; Fibrinogen; UGFS